Intelligence machine for all / Nur Amira Ghazali...[et al.] - Ghazali, Nur Amira; Hussin, Nurfadhilah; Sabri, Noor Syahidah; Ahmad Zainori, Nur Syafiqah (2019)
This blueprint report is discussed about the team are going to apply for a grant to develop a product. The product that being develop is Intelligence Machine for All. This product is a machine that has been renovated from a vending machine to a donation machine. The public can use this machine to donate something like essential needs and others using this machine. As for the description of the product, the technology description, market research and analysis, management team, the financial plan and the project milestone will be further discussed in the next chapter.